Antimicrobial consumption in food animals in Fiji: Analysis of the 2017 to 2021 import data - Magiri, Royford; Dissanayake, Chaminda; Okello, Walter (Frontiers in Antibiotics, 2022)
Abstract Globally, the demand for animal protein for human consumption has been increasing at a faster rate in the last 5 to 10 decades resulting in increased antimicrobial use in food producing animals. Antimicrobials are frequently used as part of modern methods of animal production, which may put more pressure on evolution of antibiotics resistance bacteria. Despite the serious negative effects on animal and human health that could result from using antibiotics, there are no assessment of antibiotics consumption by the livestock sector in Fiji as well as other Pacific Island Countries. The objective of this study was to quantify antimicrobials imported for use in food animals into Fiji from 2017 to 2021. Data on imported antimicrobials was obtained from Biosecurity Authority Fiji (BAF). Imported antimicrobials were then analyzed by antimicrobial class, and importance to veterinary and human medicine. An average of 92.86 kg per year (sd = 64.12) of antimicrobials was imported into Fiji in the 2017-2021 study period. The mean amount of imported active antimicrobial ingredients after adjusting for animal biomass was 0.86 mg/kg (sd = 0.59). The most commonly imported antimicrobials were penicillin’s (69.72% of the total imported antimicrobials from 2017 to 2022) and tetracyclines (15.95% of the total imported antimicrobials from 2017 to 2022). Additionally, the study found that veterinary critically important antimicrobials (96.48% of antimicrobials of veterinary importance) were the most imported and fluroquinolones, macrolides, and penicillins were the critically important antimicrobials of human importance that were imported. The study concluded that use of antimicrobials in food producing animals is low but monitoring of antimicrobial use and AMR was critical in Fiji due to overreliance on antimicrobials of last resort.